Clinicopathological Study of Salivary Gland Tumors - Khedkar, Somnath Sangram; Bhandari, Anup Pravin; Shirgaonkar, Nilesh Pradip (Annals of Pathology and Laboratory Medicine, 2020)
Background: Salivary gland tumors represent the most complex and diverse group of tumors, diagnosis and management of which is complicated by their relative infrequency, the limited amount of pretreatment information available and the wide range of biologic behavior seen with the different pathologic lesions. However, there are no reliable criteria to differentiate, on clinical grounds the benign from the malignant lesions and morphologic evaluation is necessary. Hence, the present study is undertaken to study the spectrum of benign and malignant tumors of salivary gland with emphasis on histopathological features. Methods: Prospective and retrospective study (2012 to 2016) comprised of Fine needle aspiration cytology (FNAC), histopathology specimens and slides received in our Department of Pathology during period of 5 years. In each patient age, sex, site and relevant clinical details were recorded in a proforma. FNAC is performed whenever possible followed by histopathological examination as gold standard for diagnosis. Results were analysed in tabular format and Sensitivity, Specificity and Diagnostic accuracy were calculated according to standard formulas. Result: During the study period of five years 60 salivary gland neoplasms were studied out of which 40 were benign, most common being pleomorphic adenoma. Most common malignant tumor was mucoepidermoid carcinoma. Mean age of presentation was 41 years. Histocytological correlation was obtained in 40 cases. Conclusion: Salivary gland tumors are relatively uncommon, and exhibit a wide variety of microscopic appearances, even within one particular lesion, and this has caused considerable problems in categorization and diagnosis. Accurate diagnosis is essential as salivary gland neoplasms have diverse clinical and prognostic outcomes.